Factors Influencing Health Service Performance at the Bulili Health Center, Palu City - Sudirman; Herlina Yusuf; Wijayanti (Universitas Muhammadiyah Palu, 2025)
Employee performance refers to the extent to which employees achieve work outcomes in accordance with predetermined job standards. Performance encompasses not only work results but also behaviors, attitudes, and mental readiness, reflecting a commitment to continuous improvement in work quality. This study aimed to analyze the determinants of health workers’ performance at the Bulili Community Health Center, Palu City, in 2024. This study employed a quantitative approach with an analytical survey design. The study population consisted of all employees at the Bulili Community Health Center, with a total sample of 80 respondents. Data were collected using a structured questionnaire measuring variables including length of service, attitude, motivation, rewards, leadership, and work performance. Data analysis was conducted using the chi-square statistical test with a significance level of ? ? 0.05, followed by multivariate analysis to identify the most influential determinant. The results indicated significant relationships between length of service and work performance (p = 0.001), attitude and work performance (p = 0.000), motivation and work performance (p = 0.000), rewards and work performance (p = 0.000), and leadership and work performance (p = 0.000). Among the five variables, leadership emerged as the most influential determinant of work performance (B = 1.795; Sig = 0.024). In conclusion, length of service, attitude, motivation, rewards, and leadership are significantly associated with the performance of health workers. Therefore, targeted efforts—particularly in strengthening leadership practices—are essential to enhance employee performance and ensure the delivery of high-quality health services.